A point prevalence study of catheter associated urinary tract infections among patients admitted in an university hospital - Binda, Filippo; Demarchi, Antonia; Galazzi, Alessandro; Nicolò, Gabriella; Bisesti, Alberto; Accardi, Roberto; Laquintana, Dario (International Journal of Research in Medical Sciences, 2019)
Background: Urinary tract infections (UTIs) are the most common type of healthcare associated infection in acute care hospitals. Most involve urinary drainage devices, such as urinary catheter. The objective of this study was to investigate the prevalence of catheter-associated urinary tract infections in adult patients of a tertiary level university hospital. Methods: The point prevalence study was conducted in one single day and included all adult patients admitted in medical, surgical wards and intensive care units. The Centre for Disease Control (CDC) criteria were adopted to classify the different type of UTIs. Results: Out of a total of 497 adult inpatients, 94 patients had a urinary catheter for at least 48 hours. The prevalence of symptomatic urinary tract infection (SUTI) in this sample is 17%. Escherichia coli (31.2%), Enterococcus faecium (25.0%) and Enterococcus faecalis (12.5%) are the most common pathogens found. Conclusions: The main isolated uropathogens in this study are Gram-negative and Escherichia coli remains one of the most frequent cause of UTIs in human. Gram-negative pathogens have multiple virulent factors responsible for their adherence to uroepithelium and urinary catheter positioning facilitates the transmission of these pathogens to urinary tract. Urinary catheterization is frequently used as solution to facilitate continence and maintain skin integrity in elderly patients. Urinary incontinence frequently is an example of inappropriate use of urinary catheter: for that reason, urinary catheter should be considered as the last option if other solution, like incontinence pads, are not indicated.